Sex-differences in age-related grip strength decline: A 10-year longitudinal study of community-living middle-aged and older Japanese - Rumi Kozakai; Fujiko Ando; Heung Youl Kim; Atsumu Yuki; Rei Otsuka; Hiroshi Shimokata (Japanese Society of Physical Fitness and Sports Medicine, 2016)
The purpose of this study was to estimate sex differences in age-related grip strength decline and describe the course of decline in grip strength from age 40 to 89 years by a longitudinal epidemiological study. Participants were randomly selected community-living men (n = 648) and women (n = 598) aged 40 to 79 years at baseline. Grip strength was measured with standard techniques every other year over a 10-year period. The preservation rate of grip strength was calculated as the 10-year follow-up value divided by the baseline value. The relationship between the preservation rates of grip strength and age group (by decade) at baseline by sex was analyzed using Two-Way Analysis of Variance and the Tukey-Kramer method. The trajectories of grip strength over 10 years were plotted for both men and women. The mean grip strength preservation rates of participants in their 40s, 50s, 60s and 70s over 10 years was 0.90, 0.88, 0.84 and 0.79 in men, and 0.89, 0.89, 0.89 and 0.88 in women, respectively. There were significant differences in sex and age group at baseline in the preservation rate of grip strength. Among men, the preservation rate of grip strength for the 70s group was significantly lower than that of younger groups (p < 0.05); however, no significant difference was observed among age groups in women. The trajectories of grip strength decline year by year were steep in men, but even in women. Age-related decline in grip strength markedly increased in older men, but remained constant throughout middle and late adulthood in women.